Socio-demographic characteristics and sexual health related attitudes and practices of men having sex with men in central and southern Malawi - Ntata, PRT; Muula, AS; Siziya, S (Tanzania Journal of Health Research, 2008)
An exploratory study of men having sex with men (MSM) was conducted in central and southern Malawi in order to understand their socio-demographic characteristics, sexual behaviours, and perceptions about confidentiality and stigma. A total of 97 men participated in the study of whom 84 (86.6%) were in the age group 17-32 years. The majority, 73 (75.3%) of MSM had never married, 26 (32.5%) reported not always using condomsduring sexual intercourse, and 23 (23.7%) had ever received money or gifts in exchange of sex. Only 17 (17.5%) of the participants reported being exposed to HIV prevention messages targeted at MSM. Fear of sexual orientation disclosure and discrimination were reported by 27 (30.7%) of MSM. Many of the study participants reported thatHIV intervention programmes are not accessible to them. In conclusion, HIV intervention programmes may not be reaching out to the majority of MSM. We suggest an exploration of the feasibility of HIV prevention interventions targeting MSM in this country where the practice is illegal. Keywords: sexual orientation, men, attitudes, practices, HIV, prevention, Malawi Tanzania Journal of Health Research Vol. 10 (3) 2008: pp. 124-130